Economic Burden of Periprosthetic Joint Infection - Mulyadi, Dicky; RMSN, Magetsari (Indonesian Hip and Knee Society (IHKS), 2023)
Total knee arthroplasties (TKAs) and total hip arthroplasties (THAs) have been proven to help improving the quality of life of numerous patients and have been regarded as successful standard operations in orthopaedic surgeries. However, there is still a lingering devastating complication in the form of peri-prosthetic joint infection (PJI). This condition can be difficult to diagnose and may present at any time after arthroplasty requiring surgical intervention, often multiple times. Surgical revisions due to infection requires multiple visits and longer length of stay resulting in greater hospital costs. As the number of arthroplasty procedures increases so does the number of PJIs and therefore revisions. In 2010 there were estimated 8 136 PJI cases associated with hips and 17 781 cases associated with the knee and it is projected to grow in 2020 to be 16 584 cases for hip and 48 971 cases for knee. This also translated in the increase of estimated cost from around 785 million in 2010 to 1.62 billion in 2020.